The Relationship Between Smoking Habits Among Pneumonia Patients and Length of Hospitalization - Tiara Anisyah Harahap; Qomariah RS; Diniwati Mukhtar (Journal La Medihealtico, 2025)
Pneumonia is a respiratory tract infection caused by viruses, fungi or bacteria. The impact of pneumonia can be measured by the length of stay (LOS) in the hospital. One of the risk factors for pneumonia is smoking. Given the high prevalence of smokers in Indonesia, this study aims to examine the correlation between smoking habits and the duration of the length of stay in pneumonia patients at RSUD dr. Chasbullah Abdulmadjid Bekasi city. This study used an analytical observational design with cross sectional approach. The research population was pneumonia patients at RSUD dr. Chasbullah Abdulmadjid, with a total of 122 patients obtained through consecutive sampling. Secondary data from patients medical record were used. Data analysis was performed using the Chi Square statistical test to determine the relationship between variables. Out of 122 patients, it was found that 50.8% (62 patients) were non smokers and 42.2% (60 patients) were active smokers. The distribution of length of stay shows that 73.8% of patients had a short length of stay category. The Chi Square test result indicated a significant relationship between smoking habits and the length of stay in pneumonia patients (P – Value 0.000). There is a statistically significant relationship between smoking habits and length of stay (LOS) in pneumonia patients.